THE SOMALISATION OF POLITICAL ISLAM: TURNING POINT FOR THE CLASH OF ISLAMISMS IN AFRICA - Ignacio Gutiérrez de Terán Gómez-Benita (Revista CIDOB d'Afers Internacionals, 2011)
This article covers – firstly and generally speaking – the gradual process of confrontation between traditional African Islam (and particularly the Sufi brotherhoods) and the Salafist tendencies that became established in the continent some time ago. Taking the chronic case of Somalia as an example, the author stresses the fact that in addition to doctrinal differences, it is also important to note that social, economic and cultural factors have also helped to aggravate tensions. These, nevertheless, have even erupted in the heart of organisations backing political Islam, in many cases of Wahhabi origin, owing partly to geostrategic determining factors, and partly to the turbulent debate on the advisability of incorporating processes of national reform and reconciliation. Furthermore, and in a way that is reminiscent of a number of antecedents in countries such as Algeria and Afghanistan, the controversy is focused around which strategy to adopt to fight the local leaders who have been labelled as corrupt, and how to link up with the regional and international powers involved in the conflict. Thus, an extreme Somalisation has also reached African Islamist movements, as can be seen in the current fragmentation of Islamism over much of the continent.